Don't count on it! - Bogle, John C. (John Wiley & Sons, 2011)
Insights into investing and leadership from the founder of The Vanguard Group Throughout his legendary career, John Bogle-founder of the Vanguard mutual fund group and creator of the first index mutual fund-has helped investors build wealth the right way, while, at the same time, leading a tireless campaign to restore common sense to the investment world. A collection of essays based on speeches delivered to professional groups and college students in recent years, in Don't Count on It is organized around eight themes. Illusion versus reality in investing. Indexing to market returns. Failures of capitalism. The flawed structure of the mutual fund industry. The spirit of entrepreneurship. What is enough in business, and in life. Advice to America's future leaders. The unforgettable characters who have shaped his career. Widely acclaimed for his role as the conscience of the mutual fund industry and a relentless advocate for individual investors, in Don't Count on It, Bogle continues to inspire, while pushing the mutual fund industry to measure up to their promise.